Kinematic modeling of transverse shear in textile composite reinforcements forming. (1st May 2023) - Chen, B.; Colmars, J.; Bai, R.; Naouar, N.; Boisse, P.
Highlights: The classical shell theory is not applicable to the transverse shear kinematics of textile composite reinforcements. A kinematic approach is presented to correct shear deformation without complicating the shell method. Experimental comparisons show that the transverse shear of multi-layer textile fabric can be modeled accurately by the proposed approach. The approach can be available for any user, together with any finite element software. Abstract: During the draping of dry textile reinforcements, the high tensile stiffness of fibers and the possible slippage between them significantly modify the transverse shear deformation mechanism. In order to show the limits of classical shell elements (Kirchhoff and Mindlin shell) for textile reinforcements, four-point bending tests of multi-layer fibrous material were conducted and analyzed through experiment and simulation. In forming cases, the mid-surface deformation was obtained by a finite element stress resultant shell, which takes the in-plane shear and bending behavior into account. Based on the quasi-inextensibility of fibers, a kinematic modeling approach was then proposed to efficiently calculate the transverse shear strain. This approach has been implemented in Matlab software as a post-processing application, and can therefore be carried out by any user, together with any finite element software. Different bending tests and hemispherical forming experiments proved the effectiveness and correctness of the approach through comparisons between experimental and numerical results. Graphical abstract: Image, graphical abstract